TUS MART Web Commerce Design As A Digital Marketing Effort For Urban Farming Products Using Kansei Engineering - Zunaidi, Rizqa Amelia; Hamidah, Dwi Nur Azizah; Putra, Perdana Suteja; Hidayati, Sri; Chandra, Huki; Mardhiana, Hawwin; Wulandari, Eka Devi (Journal of Digital Marketing and Halal Industry, 2024)
This study focused on agricultural products, utilizing the Kansei Engineering methodology to enhance user experience and align with digital marketing strategies. Kansei Engineering is applied to transform users' emotional needs into concrete design elements, creating a website interface that meets both functional and emotional requirements. By emphasizing attributes like engagement, transparency, interactivity, and ease of use, the website aims to provide a personalized, intuitive, and satisfying experience, fostering user connection and loyalty. The results demonstrate that Kansei Engineering significantly enhances emotional satisfaction and functional effectiveness, positively impacting customer engagement and retention—key elements in digital marketing. In this study, the "Refreshing" concept is tested by considering elements such as engagement, dynamism, transparency, interactivity, and ease of use to ensure that the designed interface provides an intuitive, adaptive, and enjoyable user experience. The testing process involves analysis using the Semantic Differential method as well as validity and reliability tests to ensure the accuracy and representativeness of the data obtained. The results show that the application of Kansei Engineering significantly enhances the quality of the e-commerce interface, both in terms of emotional satisfaction and functional effectiveness, resulting in a more holistic user experience. This study offers valuable insights for future e-commerce interface design, suggesting that integrating emotionally responsive design elements can boost the success of digital marketing efforts, especially in the competitive agriculture e-commerce sector.